Optimizing the Science Literacy Abilities of Elementary School Teacher Education Students Through Electrical Material Practicum - Gita Senja Sari; Ali Mustadi; Ikhlasul Ardi Nugroho; Kintan Limiansih (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to determine the optimization of students' scientific literacy abilities through practical electricity material. The sample in this research was Elementary School Teacher Education students. This research uses a quantitative descriptive approach with a survey method. The research results show that students' scientific literacy is 64.49%, which is categorized as moderate. Based on the results of a review of research results, the competency that is classified as low is competency b with a score of 65.05 and the highest competency is competency c with a score of 73.45. In this research, the indicator that needs to be improved in scientific literacy is indicator 4 at 38.5%.